2017
DOI: 10.1093/ejcts/ezx418
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 5-year follow-up study after limited resection for lung cancer with ground-glass opacity

Abstract: With these criteria, limited resection was performed safely without any recurrence, and the postoperative pulmonary function was well preserved. The outcomes of limited resection for small-sized lung cancer with GGOs that met the criteria of this study were satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…Poor prognosis was related to larger size and solidity of the main tumour (13). In a recent series of 53 patients whose lesions had a mean GGO ratio of 95.9%, all tumours were intraoperatively diagnosed as BAC and the 5-year overall survival rates were 100% even though wedge resection was preferred (14).…”
Section: Multifocal Lung Adenocarcinoma: Gg/l Multiple Subsolid Nodumentioning
confidence: 99%
“…Poor prognosis was related to larger size and solidity of the main tumour (13). In a recent series of 53 patients whose lesions had a mean GGO ratio of 95.9%, all tumours were intraoperatively diagnosed as BAC and the 5-year overall survival rates were 100% even though wedge resection was preferred (14).…”
Section: Multifocal Lung Adenocarcinoma: Gg/l Multiple Subsolid Nodumentioning
confidence: 99%
“…Firstly, compared with previous study, more recently published SEER data were used in our study. In the past years, more and more ground glass-opacity nodules were detected, and several studies showed satisfactory survivalwere obtained after limited resection among these patients [15][16][17][18]. The different composition of histology may result in different survival status in our study.…”
Section: Discussionmentioning
confidence: 54%
“…The present standard surgical procedure for lung cancer is pulmonary lobectomy with hilar and mediastinal node dissection, based on reports indicating that patients treated with limited resection for cT1N0M0 peripheral lung cancer had a worse prognosis than those treated with pulmonary lobectomy and lymph node dissection [3]. On the other hand, a prospective study reported no recurrence of the primary lung cancer during a 5-year follow-up after limited resection of lung cancer with a maximum tumor diameter of 8-20 mm, a GGO ratio >80% in a CT scan, and clinical T1N0M0; moreover, the 5-year disease-specific and overall survival rates were 100% and 98%, respectively [1]. At our institution, radical and anatomical pulmonary segmentectomies in cases of lung cancers are performed for pulmonary nodules with diameters <20 mm and GGO ratios >50% in a CT scan.…”
Section: Commentmentioning
confidence: 98%
“…The number of radical and anatomical pulmonary segmentectomies performed in cases of early lung cancers with small tumor sizes has been increasing recently in Japan [1,2]. Segmentectomy is useful for preserving respiratory function; however, the rate of local recurrence of lung cancer is higher for segmentectomy than for lobectomy [3].…”
mentioning
confidence: 99%